Vertical transport, growth processes, and aerosol characterization in Amazonia - Franco, Marco Aurélio de Menezes (2021)
The Amazon Tall Tower Observatory (ATTO) is a laboratory located in a primary forest region in the Central Amazon, ideal for studying the aerosol properties in the vertical profile, particularly at heights of 60 and 325 m from the ground. In this work, we identify and characterize the processes that control the aerosol population, their physicochemical properties, and the growth of particles in the vertical profile of the boundary layer. Measurements of particle number size distribution, scattering, and radiation absorption were used and the chemical composition of aerosols, together with remote sensing data. The analysis of the occurrence of aerosol particles growth was focused on particles from 10 to 50 nm, with measurements between February 2014 and September 2020. It was observed that in 14 % of the analyzed period (217 in 1596 days) we identified particle growth events, with 88 % of them occurring in the wet season. The diurnal cycle of growth frequency showed that 74 % of them occur during the day, indicating an association with photochemistry and boundary layer evolution. The median growth event rate was 5.2 nm/h, and the condensation sink during growth was 0.0011/s. The relationship of growth events with meteorological variables showed that most event onsets coincide with the occurrence of descending convective currents (63 %). The aerosol chemical composition is mainly dominated by the organic fraction, with 80 % of the mass of PM1. Organic aerosols are determinants of the aerosol scattering coefficient. The average absorption and scattering coefficients, abs,637nm and scat,525nm, under atmospheric conditions without significant anthropogenic impacts were 0.14/Mm and 4.4/Mm, respectively. Apparent differences in aerosol physical properties between 60 and 325 m in height were observed for scat,525nm, and aerosol volume. A strong spectral dependence of the mass scattering efficiencies with the incident radiation wavelength was observed, and, in particular, they were significantly larger at 60 m, showing that the aerosol population close to the canopy is more effective in scattering the radiation. In contrast the mass absorption efficiency is similar at the two heights. It was observed that the concentration of aerosols smaller than 50 nm increases with increasing convective activity and lightning occurrence. It was observed that 72 % of aerosol particle transport events occur first at 325 m, which is expected for processes dominated by convective downward currents. In contrast 28 % of the events started at 60 m, and only later were detected at 325 m. The results support the hypothesis of a source of aerosols smaller than 50 nm close to the canopy. We show that the physical characteristics of aerosols at heights of 60 and 325 m are different, with those closest to the canopy being dominated by biogenic emissions and those at 325 m being more processed and influenced by long-range transport.